Dentin to dentin adhesion using combinations of resin cements and adhesives from different manufacturers - a novel approach - Elke Seitz; Carl Hjortsjö; Jon E. Dahl; Erik Saxegaard (Medical Journals Sweden, 2020)
Aims The aims of this study were to present a novel method to analyse dentin bond strength and to evaluate the bond strength of combining adhesive systems and resin cement from different manufacturers. Methods Human wisdom teeth were ground flat to the dentin on parallel surfaces and axially cut into two parts. Dentin cylinders (Ø 3 mm) were drilled from one half of each tooth. The other half from each tooth was embedded in epoxy resin with the dentin surface exposed. The specimens were ground with silicone carbide paper and the dentin cylinders were cemented onto the dentin surface of the other half of the same tooth. Materials: Resin cement and adhesive systems from three different manufacturers were used in various combinations (n = 8 per group). Cement and adhesive from the same manufacturer served as control. Shear bond strength (SBS) was measured and fracture modes were registered. Results and conclusions: The highest median SBS value was found in a bonding combination between cement and a non-corresponding adhesive (33.1 MPa) and one of the lowest values was found in one of the controls (15.3 MPa). Cohesive fractures were most frequent. The results indicated that combining adhesive and cement from different manufacturers did not compromise the dentin bonding. The novel test method is recommended for evaluating dentin bonding.